Petani Tembakau dalam Genduk sebagai Realitas Sosial: Tinjauan Sosiologi Sastra: Tobacco farmers in Genduk as a social reality: a review of sociology literature - Riswari, Aninditya Ardhana (Journal of Literature and Education, 2024)
This study was structured with the aim of analyzing the existence of tobacco farmers in Genduk as a social reality through a sociological review of literature. This study uses a qualitative descriptive research method that focuses on the sociology of literature approach through Wellek and Warren's sociology combined with the concept of social reality. The results of the study show that the tobacco farmers in Genduk are not mere works of fiction, but instead Genduk is the bearer of the "message" conveyed by the author about the life story of tobacco farmers on the slopes of Mount Sindoro. The social reality conveyed by the author is known to refer to objective reality, as a result of the author's thought on the experience he has gone through as a native of Temanggung, Central Java, who also has a life story on the slopes of Mount Sindoro. Therefore it can be concluded that the tobacco farmers in Genduk are a social reality resulting from the thought of reality combined with social phenomena, which refers to the essence of humanity.